2016
DOI: 10.3354/dao02983
|View full text |Cite
|
Sign up to set email alerts
|

Management of severe head injury with brain exposure in three loggerhead sea turtles Caretta caretta

Abstract: The loggerhead Caretta caretta is the most common sea turtle in the Mediterranean. Currently, sea turtles are considered endangered, mainly due to the impact of human activities. Among traumatic lesions, those involving the skull, if complicated by brain exposure, are often life-threatening. In these cases, death could be the outcome of direct trauma of the cerebral tissue or of secondary meningoencephalitis. This uncontrolled study aims to evaluate the use of a plantderived dressing (1 Primary Wound Dressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
(27 reference statements)
0
8
0
3
Order By: Relevance
“…However, gentamicin can induce nephrotoxicity, which may lead to acute renal failure [ 36 ]. Recently, plant-derived commercial dressing has been reported for use in loggerhead turtles with entanglement or severe head injury [ 37 , 38 ]. From the results in this study, we suggested that aminoglycosides together with plant-derived commercial dressing may be considered as a protocol to be used for treatment of bacterial infection in juvenile sea turtles at STCCT.…”
Section: Discussionmentioning
confidence: 99%
“…However, gentamicin can induce nephrotoxicity, which may lead to acute renal failure [ 36 ]. Recently, plant-derived commercial dressing has been reported for use in loggerhead turtles with entanglement or severe head injury [ 37 , 38 ]. From the results in this study, we suggested that aminoglycosides together with plant-derived commercial dressing may be considered as a protocol to be used for treatment of bacterial infection in juvenile sea turtles at STCCT.…”
Section: Discussionmentioning
confidence: 99%
“…Several diseases involving the head of sea turtles have been reported. Bone fractures complicated by brain exposure, meningeal hemorrhages, and heterophilic meningoencephalitis due to traumatic lesions mainly caused by boat strikes have been reported [ 28 , 31 , 33 , 39 ]; unassisted mortality rate has been recently used as a quality indicator parameter in the rehabilitation of loggerhead turtles, and the highest value was found in the trauma (boat strikes) category, suggesting a poor prognosis for these turtles [ 6 ]. Meningitis and encephalitis caused by trematode eggs and adult trematodes have also been described [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The head of the sea turtle is susceptible to congenital, developmental, traumatic, and infectious disorders [ 28 , 29 , 30 , 31 , 32 , 33 ]. An accurate interpretation and thorough understanding of the anatomy of this region could be useful for veterinary practice on sea turtles.…”
Section: Introductionmentioning
confidence: 99%
“…Among the different threats, traumatic injuries to sea turtles are common and can occur from many anthropogenic causes such as watercraft, fishing activity or water controlling equipment, but also predation such as bites from shark or conspecific 1 . The most common sea turtle injuries reported in the literature are head trauma, carapace fractures and flipper lacerations 2 . When tissue damage to a flipper is severe, partial or complete amputation is generally considered 3 .…”
Section: Introductionmentioning
confidence: 99%
“…1 The most common sea turtle injuries reported in the literature are head trauma, carapace fractures and flipper lacerations. 2 When tissue damage to a flipper is severe, partial or complete amputation is generally considered. 3 After single amputation, sea turtles retain remarkable swimming and maneuvering ability, thus release can be expected.…”
Section: Introductionmentioning
confidence: 99%